Canada Should Retain Its Reservation on the United Nation's Convention on the Rights of Persons with Disabilities. (December 2018) - Dufour, Mathieu; Hastings, Thomas; O'Reilly, Richard
The United Nations adopted the Convention on the Rights of Persons with Disabilities (CRPD) in 2006. When Canada ratified the CRPD, it reserved the right to continue using substitute decision making schemes even if the CRPD was 'interpreted as requiring their elimination'. This was a prescient decision because the CRPD Committee, which is tasked with overseeing the interpretation and implementation of the CRPD, subsequently opined that all legislation supporting substitute decision making schemes contravene the CRPD and must be revoked. The CRPD Committee insists that every person can make decisions with sufficient support and that if a person lacks capacity to make a decision, we must rely on their 'will and preferences'. Many international legal scholars have called this interpretation unrealistic. We agree and, in this article, describe how this unrealistic approach would result in extensive harm and suffering for people with severe cognitive or psychotic disorders. The reader should also be aware that the CRPD Committee also calls for the elimination of all mental health acts and the United Nations Commissioner for Human Rights for the abandonment of the not criminally responsible (NCR) defence.